Designing Effective Experiential Curriculum: The Experiential Learning Map - Saggar, Maya; McArdle, John; de Koning, Alice; Choudhary, Anjali (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
Designing experiential student exercises or course modules can be a daunting task for faculty members. Often, not knowing where to begin is a barrier that causes instructors to avoid developing meaningful, high-impact student exercises grounded in experience. Yet, we know that these can be incredibly powerful and transformative pedagogies. The Experiential Learning Map (ELM) is a curricular planning tool that instructors, learning consultants, or students can use to storyboard and develop an experiential lesson. Modelled after best practices in business model ideation, and informed by research about experiential learning, the ELM provides instructors with an easy-to-use curriculum planning tool. The ELM is designed to be flexible. Instructors can scale the pedagogy from a single-class interaction to a multi-session pedagogical arc. The ELM's value is that it provides instructors with a simple, iterative planning tool that can be used to scope and scale a learning experience.